Lactobacillus-Based Probiotics Reduce the Adverse Effects of Stress in Rodents: A Meta-analysis - Mindus, Claire; Ellis, Jennifer; van Staaveren, Nienke; Harlander-Matauschek, Alexandra (Frontiers in Behavioral Neuroscience, 2021)
Lactobacillus species play a critical role in the bidirectional communication between the gut and the brain. Consequently, they have the potential to aid in the treatment of psychological disorders. The impact of Lactobacillus supplementation on the response to stressful situations that can trigger psychological disorders is not systematically reviewed. Therefore, the aim of this meta-analysis is to summarize the body of research assessing the effects of Lactobacillus-based probiotics in stressed and non-stressed rodents. The duration of immobility in a Forced Swim Test (FST) was the outcome used to measure changes induced by various treatments. Four online databases were systematically searched for relevant studies published in English. Fourteen studies met the criteria and were included in the meta-analysis. The effects of probiotic supplementation and stress treatment on the duration of immobility in the FST were analyzed using a generalized linear mixed model. Publication bias was evaluated by funnel plots. Our analysis shows that Lactobacillus-based probiotic supplements significantly reduce immobility in the FST (P < 0.001) in a stressed population. However, probiotics did not affect the non-stressed population (P=0.168). These findings provide a better understanding of Lactobacillus-based probiotics for the management of stress-induced behavior.